Common Venues in Romantic Relationships of Adults With Symptoms of Autism and Attention Deficit/Hyperactivity Disorder - Soares, Lorrayne Stephane; Alves, Ana Luiza Costa; Costa, Danielle de Souza; Malloy-Diniz, Leandro Fernandes; Paula, Jonas Jardim de; Romano-Silva, Marco Aurélio; Miranda, Débora Marques de (Frontiers in Psychiatry, 2021)
Introduction: Autism Spectrum Disorder (ASD) and Attention Deficit/Hyperactivity Disorder (ADHD) figures among the most common neurodevelopmental disorders. Despite having opposite stereotypes, both ADHD and ASD compromise, though in different ways, skills such as social interactions, communication skills, and social thinking, which may underlie difficulties in romantic relationships. Methods: We evaluated 306 adults about their romantic relationships and the intensity of their love. Participants were from one of four groups:, individuals with ASD-only traits, a group with symptoms of ADHD-only, participants with neither ADHD nor ASD symptoms (control) or from a fourth group of individuals withboth ADHD and ASD traits. Results: The ASD traits group had fewer married people and more people who have never been married, while the rate of divorce was higher in the ADHD traits group. Regarding the intensity of love, the mean scores of the ADHD and the ADHD+ASD traits groups were higher in the Passionate Love Scale than the mean score of the control group. Passionate love in the ASD group was no different from the other groups. Small positive correlations were found between passionate love and ADHD and ASD behavioral problems. Conclusion: Marital status was distinct depending on symptoms of a neurodevelopmental disorder in adulthood. Also, ADHD and ASD symptoms were associated with greater passionate love. Therefore, ADHD and ASD behavioral dimensions may impact long-term and short-term experiences of a person's relationship with a significant other in distinct ways. Understanding how people with neurodevelopmental disorders experience love might help us to better clarify the mechanisms associated with their relationship patterns.